Investigation of the dependence structure between imports and manufacturing production index of Thailand using copula-based GARCH model - Chakorn Praprom (2018)
© 2014 by the Mathematical Association of Thailand. All rights reserved. This paper aims at investigating the dependence structure between the imports and the manufacturing production index of Thailand using a copula-GARCH approach. We applied skewed student-t distribution to estimate all of the marginal distributions with ARMA(1,12)-GARCH(1,1), ARMA(1,2)-GARCH(1,1)to fit the manufacturing production index (MPI) and the imports of Thailand. The results of this paper suggest that the student-t copula is the most appropriate method to best t the tail dependences in both static and time-varying copulas because the AIC and the BIC of this method are the lowest when compared with the candidates among the other types of copula.